A descriptive analysis of intercultural content of the EFL textbooks used in the intermediate schools in Iraq - Obaid, Ali Abdulridha; Ismail, Lilliati; Mohamed Razali, Abu Bakar; Mansor, Nor Shahila (Human Resource Management Academic Research Society, 2019)
Integrating culture in ELT, particularly in EFL textbooks, has recently gained greater importance and attention based on both the sociocultural theory that portraits learning as a social action, and the conception that culture and language are unavoidably attached. It has also come to be more important because English is an international language and a lingua Franca in the twenty-first era of globalization. Accordingly, new orientations in ELT have arisen such as improving the intercultural competence. Since 2012, Iraq have adopted “English for Iraq” (EFI) series of textbooks which seem to lack orientations towards intercultural competence. This paper aims at finding out how the intercultural materials of EFI textbook are presented and whether they develop the Iraqi learners’ intercultural competence. Based on an adapted version of Byram’s (1997) model, a descriptive content analysis is utilized to examine the texts and visuals in the three textbooks used in intermediate schools. Findings indicate that intercultural elements in the textbooks show sharp differences in their frequency of occurrences portraying an imbalanced intercultural presentation with a knowledge-oriented majority of mainly fact-stating materials. As such, the authors found that these textbooks do not improve the Iraqi EFL learners’ intercultural competence. The paper has educational implications in concern of reconsidering culture integration in the Iraqi EFL textbooks so as to cope with the recent trends and objectives in ELT to promote the students’ empathy, tolerance, and respect of otherness.